Digital and Gamified Intervention to Promote Well-Being in Early Childhood: A Feasibility Study - Raj, Habib (My University, 2025)
Family-centered interventions can promote early childhood well-being and improve health literacy. A WellWe intervention was developed to improve parental self-efficacy and children's healthy behavior in early childhood. WellWe intervention is a theory-driven, evidence-based, and family-centered web-based intervention. It was designed for families with 1.5 to 4-year-old children and for public health nurses (PHNs) to initiate health discussions at child health clinics during the extensive health visits. Before implementation, evaluating the feasibility of digital health intervention is essential to ensure its acceptability and usability by different users. Therefore, this study explored the feasibility of integrating the WellWe intervention into existing care delivery systems and services to improve health outcomes. The first objective of this study was to use a qualitative approach to evaluate the usability and acceptability of the WellWe intervention from the perspectives of PHNs and families. The second objective was to use a quantitative approach to identify the initial effectiveness of the WellWe intervention in improving parental self-efficacy regarding children's health outcomes. This study was conducted in Southwest Finland during 2017-2018, and it contains two parts: qualitative feasibility testing (part 1) and a quasi-experimental study (part 2). During part 1, a semi-structured in-depth interview was conducted among the PHNs (n=5) and parents with children 1.5 – 4 years old (n=15). This study also explored the practical barriers to using the intervention and recommended strategies for the future improvement of the WellWe intervention. In part 2, a quasi-experimental research design was followed to test the initial effectiveness of the WellWe intervention based on the families' changing self-efficacy in children's healthy eating habits and physical activity over time at three different time points (baseline, immediately after the intervention and 4 months after the health examination as a follow-up) after using the WellWe intervention. Participating parents with children 1.5 – 4 years old were allocated either to an intervention group (n=15) or a control group (n=21) Both qualitative and quantitative results suggested that WellWe is an acceptable intervention. In addition, PHNs and parents showed positive experiences using this intervention. Therefore, the WellWe intervention appeared to be an appropriate early childhood health promotion tool. However, future development should be made based on the feedback, and a cluster randomized controlled study should be planned to assess the effectiveness of the intervention.
Keywords: WellWe intervention, Early Childhood, Well-being, Feasibility Study, Health Promotion, Digital and Gamified Intervention.